Campaign Finance Reform and the Problems with the Citizens United v. Federal Election Commission Supreme Court Case. - Merrin, Jacob J. (Tufts University. Tisch Library., 2005)
Tisch Library Undergraduate Research Award Winner, 2013. In 2010, the conservative leaning Supreme Court, in the name of free speech, made one of the largest misjudgments in its history, namely the abolishment of campaign finance reform. (Citizens United v. Federal Election Commission) In Citizens United v. Federal Election Commission, the Court ruled that, among other things, it was unconstitutional to prohibit corporations from indirectly supporting political campaigns or restricting the amount of money they could contribute to said campaigns. In addition, the Court legalized indirect contributions by trade associations, of which foreign institutions may be members. (Citizens United v. Federal Election Commission) As a result of this judicial action, the Citizens United ruling exposed the American political system to financial corruption and international influence.